PENERAPAN METODE DEBAT GUNA MENGEMBANGKAN SIKAP KRITIS DAN KETERAMPILAN BERARGUMENTASI MAHASISWA - Petir Pudjantoro (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: this study is the implementation of lesson study that tried to apply the method of debate in political sociology course. Lesson study activities use to three proccess, plan, do, and see. Debate methods purpose to develop the ability to think critically, rationally and creatively to address current issues of politic and citizenship. Through the application of the method of debate in the course, students examine issues of developing the interaction between state and society in the context of political communication. Learning debate practice speaking skills and behave intelligently so as to form a personal democratic and accountable. Through this lesson, learners have different readiness views and have the skills to resolve any issues and differences.Keywords: method of debate, critical attitude, skills of the students argued